Improving Thematic Learning Outcomes Through Media Crosswords in Grade VI Elementary School Students - Rina, Betty Fajar (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The learning conducted by teachers should utilize enjoyable learning media to attract students' attention. Based on the teacher's reflection, the thematic learning outcomes of the students are still low. The research aims to improve thematic learning outcomes through the use of crossword puzzle media for sixth-grade students at SD Negeri 1 Kebonbimo. This study was carried out in three cycles, each consisting of four stages: planning, implementation, observation, and reflection. The cycles were stopped when the average student learning outcomes indicator reached 85.00. The research results showed that the average learning outcomes in cycle 1 were 65.00, in cycle 2, it was 76.43, and in cycle 3, it reached 90.00. The results indicated a significant increase in cycles 2 and 3. Thus, it can be concluded that using crossword puzzle media can enhance thematic learning outcomes for sixth-grade students.